European Yearbook of International Economic Law 2013
XX, 602 p.
Keywords: Part one of Volume 4 (2013) of the European Yearbook of International Economic Law offers a special focus on recent developments in international competition policy and law. International competition law has only begun to emerge as a distinct subfield of international economic law in recent years, even though international agreements on competition co-operation date back to the 1970s. Competition law became a prominent subject of political and academic debates in the late 1990s when competition and trade were discussed as one of the Singapore issues in the WTO. Today, international competition law is a complex and multi-layered system of rules and principles encompassing not only the external application of domestic competition law and traditional bilateral co-operation agreements, but also competition provisions in regional trade agreements and non-binding guidelines and standards. Furthermore, the relevance of competition law for developing countries and the relationship between competition law and public services are the subject of heated debates. The contributions to this volume reflect the growing diversity of the issues and elements of international competition law.